Description of a thermodynamic ocean modelling system TOMS - Jensen, Tommy G., author (Colorado State University. Libraries, 1998)
A new quasi-isopycnal ocean model is presented. The model has full prognostic equations for momentum, temperature, salinity and tracers. Bottom topography can be included or the model can be used in a reduced gravity upper ocean mode. As an option, the model can be run without prognostic thermodynamics. An arbitrary Lagrangian-Eulerian (ALE) coordinate is used in the vertical, making the model a hybrid between a traditional z-coordinate model and an isopycnal model. In the horizontal, spherical coordinates or rectangular coordinates may be used. The mixed layer formulation is of Kraus-Turner type with added entrainment due to shear. Vertical diffusion of momentum, heat, salt and other tracers is incorporated using a Richardson number dependent formulation. Horizontal diffusion can be any combination of harmonic and biharmonic friction. The coastlines can be irregular and have open boundaries. Many open boundary conditions are available. Test results for oceanic upwelling regimes are given.
December 1998.
Keywords: Ocean-atmosphere interaction; Ocean circulation